2016
DOI: 10.1038/srep38648
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of virulence potential of uncharacterized Enterococcus faecalis strains using pan genomic approach – Identification of pathogen–specific and habitat-specific genes

Abstract: Enterococcus faecalis, a leading nosocomial pathogen and yet a prominent member of gut microbiome, lacks clear demarcation between pathogenic and non-pathogenic strains at genome level. Here we present the comparative genome analysis of 36 E. faecalis strains with different pathogenic features and from different body-habitats. This study begins by addressing the genome dynamics, which shows that the pan-genome of E. faecalis is still open, though the core genome is nearly saturated. We identified eight unchara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 59 publications
3
11
0
Order By: Relevance
“…These results are in accordance with the previous study for E. faecium genome [36]. The small size of core genome and huge number of accessory genes support the observation of the genomic fluidity in E. faecium [37]. …”
Section: Discussionsupporting
confidence: 93%
“…These results are in accordance with the previous study for E. faecium genome [36]. The small size of core genome and huge number of accessory genes support the observation of the genomic fluidity in E. faecium [37]. …”
Section: Discussionsupporting
confidence: 93%
“…Genomic analysis of commensal and infection-associated E. faecalis strains reveals a highly conserved (in terms of both synteny and protein sequences) core of approximately 2,500 genes, with a preponderance of additional mobile elements (plasmids, transposons [Tns], and genomic islands) encoding antibiotic resistance and suspected virulence determinants involved in hospital outbreaks ( 4 , 5 ). Recently, an elegant phylogenetic analysis of genome sequences from 24 diverse enterococcal species and five closely related nonenterococcal species suggested that enterococci have coevolved as GI tract commensals with terrestrial animals since the time of their divergence from fish ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the analysis conducted here has shown that pan-genome of E. faecium constructed on the basis of 10 genomes is still open, while the core genome seems to have reached almost a closed state. The small size of the core genome and a huge number of accessory genes support the observation of the genomic fluidity of E. faecium (Bakshi et al 2016).…”
Section: Resultsmentioning
confidence: 59%